An Analysis of Automatic Voice Recognition and Speaker Identification Algorithms and its Applications - Sethuraman, Ram; Selvin Paul Peter, J; Reddy Middela, Shanthan; ., . (International Journal of Engineering and Technology, 2018)
Voice recognition is the domain which is used to identify the speaker behind a speech through their voice. In the field of research, Voice recognition is a domain which has been widely explored by data mining experts and used for various applications. The features of the voice are extracted through methods like MFCC and then various Data Mining and Machine learning algorithms are applied for each specific application. Researchers have explored and tested the efficiencies of various algorithms for various purposes. There appears to be specific algorithms which outperform the rest in certain applications whereas they tend to perform badly for certain other applications. This paper aims to discuss the various Voice recognition techniques and its uses in various domains. The work aims in providing the characteristics and limitations of these approaches. Â